EFFECT OF SEEDING RATE , REPEATED CUTTINGS AND HERBICIDE ON CONTROLLING OF WEEDS IN ALFALFA FIELD Medicago sativa .L . - Salim .Hommadi.Anter (Mesopotamia Journal of Agriculture)
The experiment was carried out at Al-Rashidya research station by using the Randomized Complete Block Design . The experiment included three factors seeding rate , herbicides and mowing . Seeding rates were ( 24 and 36 kg seeds / ha) , the application of herbicides was (Trifluralen 1152 g . a . i/ha) , ( 2,4-DB 520 g a.i / ha ) , (Fuzilade 250 g a.i/ ha) and (Halloxyphop 81 g a.i /ha) besides hand weeding and check treatment . The samples were collected six times in Autumn and six in Spring . The number of branches / plant increased with the decrease of seeding rate and there was a significant increase in the forage dry weight at 36 kg/ha seeding rate . The Trifluralen caused decrease in the dodder and weeds dry weight especially in the first and second mowing , whereas 2,4-DB had clearly affected the broad leaf weeds . Fuzilade and Halloxyphop herbicides significantly affected the grasses by 100 % control of weeds in the first mowing . The weeds significantly with continuing mowing .